Conditional constructions in Makary Kotoko - Sean Allison (LibraryPress@UF, 2017)
Kotoko is a Chadic language spoken in Cameroon, in the region just south of Lake Chad. Based on an analysis of a corpus of texts with helpful input from a mother tongue speaker of the language, this paper presents the forms and functions of conditional constructions. Like other Chadic languages (Frajzyngier 1996: 313, 327), conditionals are formally indistinguishable from certain types of temporal constructions. However, unlike other Chadic languages (e.g. Hausa, Baraïn, Lamang, Miya, Goemai, Buwal), Makary Kotoko has no overt marker for the protasis comparable to ‘if’ in English. Instead, the protasis and apodosis are joined by the marker aro ‘then’ which is semantically linked to the apodosis, but is often prosodically realized at the end of the protasis. Conditional constructions are categorized by their semantics based on classifications by Taylor (1997) and Thompson, Longacre & Hwang (2007), and the function of conditional constructions within discourse is explored.